Intimate Partner Violence and Child Custody Evaluation: A Model for Preliminary Clinical Intervention - Gennari, Marialuisa; Tamanza, Giancarlo; Molgora, Sara (Frontiers in Psychology, 2018)
Intimate partner violence is defined by the World Health Organization as “any behavior within an intimate relationship that causes physical, psychological, or sexual harm to those in the relationship” and it refers to a specific relationship dynamic. In recent decades, an increasing number of studies have focused on this phenomenon, considering its exponential growth over time. Many studies have focused on risk factors for violence within the couple relationship. This paper specifically analyses the association between violence and separation or divorce. Although many interventions have been developed over the years, the effectiveness of extant interventions on violent behaviors is not yet empirically supported. Since clinical experience allows to affirm that both partners can be involved in treatment for intimate partner violence especially during mandated proceedings, the present study focuses on domestic violence in separated couples involved in a child custody evaluation process. In this case, literature supports the need for individualized assessment in order to promote the best intervention according to the specific conditions of each partner, whether the battered one or the perpetrator. However, little research has been done on child custody evaluation in the presence of violent couples. The aim of the present study is to present a model of couple clinical intervention with a separated violent couple in the context of a child custody evaluation. This model can be defined as relational-intergenerational and its main aim is to understand the exchange between familial generations and to search for factors that safeguard and care for family relations. Furthermore, according also to the therapeutic assessment approach, there is an intrinsic connection between assessment and “family transformative potential.” This paper presents the specific working methodology underlying this model, through the description of a single clinical case. In particular, the proposed model provides a multi-dimensional assessment comprising three levels: individual, evaluating parents' history through representations, thoughts, and feelings; interpersonal, investigating the different relations; discussion and dialogue with the parental couple about findings.